Do Good Corporate Governance and Whistleblowing Systems in Bank Industry Effectively Support Fraud Detection and Prevention? - Andrew Christian Sudjono (Association of Certified Fraud Examiners Indonesia Chapter, 2023)
Fraud can damage a business organization, and it might threaten the goals and targets achievement. It is very important to implement an effective strategy for detecting and preventing fraud. This research measures how good corporate governance principles, represented by the board of commissioners (BoC), audit committee (AC), internal audit units, and also whistleblowing system support fraud detection and prevention in banking companies. The data is analyzed using SMART-PLS with a total of 8 banks’ data for seven years from 2015 to 2021. It is found that good corporate governance executors affect the WBS by 51.3%, while fraud detection is affected both by the good corporate governance mechanism and the whistleblowing system by 37.5%. Both the board of commissioners and audit committee were found to affect the whistleblowing system, while internal audit units don’t. In contrast to this, fraud is affected by internal audit units and whistleblowing systems. Both regulators and companies must realize that both the human aspect and technology aspect, each represented by GCG principles and whistleblowing system have an important effect on fraud detection.